Antioxidants and infertility treatment, the role of Satureja Khuzestanica: A mini-systematic review - Mansoor Rastegarpanah; Tahereh Safarnavadeh (Shahid Sadoughi University of Medical Science, Yazd, Iran, 2011)
Background: The use of antioxidants in the treatment of infertility has been suggested and recent studies have indicated that oral administration of Satureja Khuzestanica essential oil (SKEO) to rats induces significant antioxidative effects.Objective: This systematic review was conducted to evaluate the effectiveness of antioxidants in infertility and also to assess the effectiveness of Satureja Khuzestanica in infertility management.Materials and Methods: Pubmed, Scopus, and Cochrane Library were searched for relevant trials published from respective database inception dates to August 2010. Study selection, and data extraction were performed by authors.Results: Fifteen trials on evaluation of antioxidants in infertility and seven studies on the effectiveness of Satureja Khuzestanica were identified. Only 4 of the 15 trials were with application of allocation concealment and three studies were done in in-vitro environment. Despite the methodological and clinical heterogeneity of the trials, 14 of the 15 (93.33%) trials showed an improvement in either sperm quality or pregnancy rate after antioxidant therapy. The human and animal studies of Satureja Khuzestanica showed a significant antioxidative potential of the plant and its effectiveness for infertility improvement.Conclusion: The use of oral antioxidants in infertility could improve sperm quality and pregnancy rates. Improved fertility observed by SKEO in rats might be due to its antioxidative effect. Further studies and clinical trials in humans are necessary to evaluate SKEO effectiveness in fertility disturbances